The Sussex-Oxford Compassion Scales : psychometric properties of the Icelandic version and correlation with well-being - María Nína Gunnarsdóttir 2000- (2023)
The study aimed to translate the Sussex-Oxford Compassion Scales (SOCS) and examine the psychometric properties of the Icelandic translation as well as their relationship to well-being. The SOCS scales measures compassion for others (SOCS-O) and self-compassion (SOCS-S). Three hypotheses were formulated. Firstly, that the factor structure of the SOCS scales would be comparable between the Icelandic and English versions. Secondly, that there would be a significant relationship between the SOCS scales and thirdly, that there would be a correlation between the SOCS scales and the WHO-5 scale, measuring well-being. Participants were 110 students from Reykjavík University, 65.5% females and 34.5% males, age 18-30+ years. Findings indicate that the Icelandic version of the SOCS scales have good psychometric properties. However, factor analysis supported a three factor solution, which is inconsistent with the proposed five factors of the original scales. The findings found a significant relationship between the SOCS-O and the SOCS-S as well as between the SOCS-S and the WHO-5 but not between the SOCS-O and the WHO-5. Keywords: compassion for others, self-compassion, well-being, psychometric properties, factor analysis. Markmið rannsóknarinnar var að þýða Sussex-Oxford Samkenndarkvarðana (SOCS) og kanna próffræðilega eiginleika íslensku þýðingar þeirra, þar að auki samband þeirra við velferð. SOCS kvarðarnir mæla samkennd í garð annarra (SOCS-O) og samkennd í eigin garð (SOCS-S). Þrjár tilgátur voru settar fram. Í fyrsta lagi, að þáttabygging SOCS kvarðanna væri sambærileg hjá íslensku og ensku útgáfunni. Í öðru lagi, að það væri marktækt samband á milli SOCS kvarðanna og í þriðja lagi, að það væri fylgni milli SOCS kvarðanna og WHO-5 kvarðans, sem mælir 3 velferð. Þátttakendur voru 110 nemendur við Háskólann í Reykjavík, 65.5% kvenkyn og 34.5% karlkyn, á aldrinum 18-30+ ára. Niðurstöður gáfu til kynna að íslenska útgáfa SOCS kvarðanna hafi góða próffræðilega eiginleika. Hinsvegar studdi þáttagreining þriggja þátta ...